The Role Of Business Environment Analysis In Marketing Crisis Management - معلا فؤاد; محمد رامي; ناصر سومر (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aimed to define the role of the business environment analysis in managing the marketing crises of Al-Hafiz company for refrigerators, freezers and household appliances, by explaining the role of both the analysis of opportunities and threats in managing the marketing crisis, the researcher relied on the deductive approach as a general approach to research, and followed the survey methodology, and distributed the questionnaire 123 individuals from the cadre of employees (consumers) in the company, and then conducted a field study for the purpose of demonstrating this relationship, and the study concluded that there is a correlation between analyzing the business environment and managing the marketing crisis; the value of the correlation coefficient reached 0.911, and this correlation is strong, how much The coefficient of determination reached 0.829, which indicates that 82.9% of the changes in the marketing crisis management follow the changes in analyzing the business environment through analyzing opportunities and threats, then some proposals and recommendations were presented to improve the relationship, the most important of which is: the company needs to present its products from multiple outlets, and the need to The company provides better quality products than other companies ’products, and the company must provide facilities in dealing with customers to obtain a greater market share, and the company must achieve an increase in the number of production units.